Determination of The Ujrah of Gold Paid Goods at Mandiri Sharia Bank (BSM) Batusangkar - Elimartati Elimartati; Muhammad Rizky Prima Sakti; Hebby Rahmatul Utamy; Utari Aulia Rifmadani (Institut Agama Islam Negeri Batusangkar, 2021)
This study analyzes the cost determination for a gold pawn ujrah at the branch of Banque Syariah Mandiri Batusangkar. This type of research is field research with qualitative methods. The analysis technique is based on the Fatwa DSN and the theory advanced by Rozalinda. The research results explain that the implementation of the gold pledge at the branch of Bank Syariah Mandiri Batusangkar in accordance with the Standar Operasional Prosedur (SOP) that have been set by the Bank. The costs of administration, maintenance and storage of the pledged goods are determined according to the amount of the customer's loan, the level of fees also depends on the amount of customer loans. So this is not in line with Fatwa DSN No. 25/DSN-MUI/III/2002 regarding Rahn, in point four, stated that maintenance and storage charges should not be based on loan amount. It is also not in line with the theory advanced by Rozalinda that the administration of administrative costs is based on the weight of the gold, the cost of maintaining and storing or renting the premises according to the content of the gold.